La presión arterial como entidad múltiple: un ensamblaje de prácticas y materialidades. - Sotelo-Daza, Jorge (Cuadernos Médico Sociales)
Objective: This article focuses on revealing where and how blood pressure is constructed, a biomedical entity that functions as a non-human actant and determines the dynamics of people’s daily lives. Methods: Qualitative, ethnographic study. Reports obtained through conversation with seven health caregivers and 28 people with high arterial blood from the city of Popayán, Colombia, were taken through the identification and monitoring of practices and the conceptual recovery of knowledge. In-depth interviews, a field diary and participant observation entangled in a praxiography were used. The concept of multiplicity was assumed considering that reality is multiplied according to the different ways in which it is put into action in different scenarios where it is built in and by practices. Results: Arterial blood emerged as a multiple entity in five scenarios of daily life: individual, family, community, health carers and the health system. It is built as a result of practices by the effect of the interaction between human and non-human entities, discourses, people, objects and materialities that are assembled and make their existence possible. Conclusions: Arterial blood is constructed (enactment) from multiple practices gathering entities of a heterogeneous nature in different scenarios of everyday life. It refers to a non-human entity that does not have a unique existence, on the contrary, it is multiple, ceasing to be a fixed and stable biomedical concept.